Public Service Management at The Command Center of The Minahasa Regency Communication and Information Service - Wattie, Lona O. K.; Masengi, Evi Elvira; Wawointana, Thelma (Technium Social Sciences Journal, 2024)
The aim of this research is to find out how Public Service Management is at the Minahasa Regency Communication and Information Service Command Center and to find out the obstacles faced by The Communication and Information Service in Public Service Management. The research method used is a qualitative method, namely answering a problem in depth in the context of the time and situation concerned, in accordance with objective conditions in the field and the type of research used is descriptive qualitative, namely describing the current state of the object qualitatively. The data sources used are primary data sources and secondary data sources with a total of 5 informants. Data collection techniques use observation, interviews, and documentation methods. The data analysis techniques used are data reduction, data presentation, and drawing conclusions. The research results show that: 1) Direct Evidence, namely providing outreach to the community and village/Regency government about the Command Center program; 2) Reliability, reliability applied in public services at the Communication and Information Service, one of which is Resources; 3) Responsiveness, which is possessed by Public Service Implementers so that it requires a process of collecting Public information in this case; 4) Guarantee, the complaint process is expected to be processed properly in accordance with the main duties and functions according to the bureaucratic structure of the Minahasa Regency Communication and Information Service (e) Empathy, The aim of the command center public service itself is to manage public complaints simply, quickly, precisely and well coordinated as a form of empathy for the community.